Influence of the Icelandic Low latitude on the frequency of Greenland tip jet events : implications for Irminger Sea convection - Bakalian, F.; Hameed, S.; Pickart, Robert S. (Journal of Geophysical Research, 2007)
Author Posting. © American Geophysical Union, 2007. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research 112 (2007): C04020, doi:10.1029/2006JC003807. The occurrence of Greenland tip jet events has been reported as the dominant factor controlling the formation of intermediate water in the Irminger Sea. It has been suggested that the frequency of these events is correlated with the North Atlantic Oscillation. To examine this process in more detail, we separate the North Atlantic Oscillation into Icelandic Low and Azores High components and carry out a regression fit of the frequency of tip jet events between 1961 and 2005. Our findings suggest that the frequency of Greenland tip jet events is highly dependent on the latitude of the Icelandic Low and the 2-year time-lagged February Icelandic Low latitude, with R2 = 0.48. We find that the winds near the southern tip of Greenland are predominately westerly during years when the Iceland Low is located above 63°N latitude. These conditions also correspond to colder air temperatures in the Labrador and Irminger Seas, implying larger oceanic heat losses due to the Greenland tip jet events and hence stronger convective overturning in the Irminger Sea. R. Pickart gratefully acknowledges support by National Science Foundation grant OCE-0450658 for this research.